Lipotoxicity pathways intersect in hepatocytes: Endoplasmic reticulum stress, c‐Jun N‐terminal kinase‐1, and death receptors. Issue 10 (15th April 2016) - Akazawa, Yuko; Nakao, Kazuhiko
Abstract : Non‐alcoholic fatty liver disease (NAFLD) is becoming increasingly more common worldwide. Hepatocyte apoptosis caused by free fatty acids, termed hepatocyte lipoapoptosis, is a feature of non‐alcoholic steatohepatitis (NASH), an advanced form of NAFLD. As no salutary treatment for NASH exists, it is important to understand the molecular mechanisms responsible for disease development and progression. This review discusses recent developments in research on hepatocyte lipoapoptosis, focusing on the endoplasmic reticulum stress, c‐Jun N‐terminal kinase‐1, and death receptor‐mediated pathway networks and their modulators and interactions. In addition, we describe the emerging importance of the signaling pathways that not only impact the dying hepatocytes themselves, but also influence surrounding cells and possibly promote disease progression through the release of microvesicles. Overall, a more comprehensive understanding of the molecular mediators in lipotoxicity‐related pathways would likely benefit the development of mechanism‐based therapies of NASH.